EKSISTENSI PTUN SEBAGAI WUJUD PERLINDUNGAN HUKUM KEPADA WARGA NEGARA DARI SIKAP TINDAK ADMINISTRASI NEGARA - Kartini, Murtiningsih; Kusyandi, Adi (Universitas Wiralodra, 2021)
All actions that harm everyone can be monitored by the court, while the review can be channeled through the State Administrative Court (PTUN). The State Administrative Court is one of the implementers of judicial power for the people seeking justice for State Administrative disputes. PTUN aims to resolve State Administrative disputes. Research methods in this papers using normative juridical research methods and using data collection techniques carried out using descriptive analysis techniques, with secondary data sources, which include primary legal materials such as laws and regulations relating to the rights of children and wives in divorce cases, sued unseen husbands, as well as secondary legal materials such as books, journals, articles, and other legal doctrines. State administrative disputes are disputes that arise in the field of State Administration between Persons or Civil Legal Entities and Legal Entities or State Administration Officials, both at the center and in the regions, as a result of the issuance of State Administrative Decrees, including employment disputes based on statutory regulations applicable. With the juridical analysis method, the author discusses the existence of PTUN as a form of legal protection for citizens from the act of state administration (abuse of power)